Use of paracetamol (acetaminophen) for suicide and nonfatal poisoning: worldwide patterns of use and misuse. - Gunnell, D; Murray, V; Hawton, K (2000)
Paracetamol (acetaminophen) is one of the most frequently used drugs in intentional overdoses. We have investigated associations between its availability and its use for overdose and suicide around the world by means of a postal questionnaire and literature review. Countries that limit the quantity of paracetamol available in a single purchase generally report lower rates of paracetamol-related morbidity and mortality. National policy decisions regarding restrictions on its availability need to weigh the inconvenience caused to the many who use the drug safely against those of the few in whom overdose may be fatal. We recommend restricting the quantity of drug available as a single purchase as the most pragmatic means of reducing paracetamol-related suicide and liver failure.